On the Solution of Multi-Dimensional Nonlinear Integral Equation with Modified Newton Method - Hameed, Hameed Husam; Eshkuvatov, Z. K.; Long, N. M. A. Nik (American Scientific Publishers, 2024)
Non-Indexed Publication